2015 IEEE International Symposium on Information Theory (ISIT) 2015
DOI: 10.1109/isit.2015.7282965
|View full text |Cite
|
Sign up to set email alerts
|

Distributed testing with zero-rate compression

Abstract: Motivated by distributed inference over big datasets problems, we study multi-terminal distributed hypothesis testing problems in which each terminal has data related to only one random variable. We consider a case of practical interest in which each terminal is allowed to send zero-rate messages to a decision maker. Subject to a constraint that the error exponent of the type 1 error probability is larger than a certain level, we characterize the best error exponent of the type 2 error probability using basic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…By (28) and the continuity of the entropy function as well as the KL divergence, we can conclude that…”
Section: 2mentioning
confidence: 90%
See 1 more Smart Citation
“…By (28) and the continuity of the entropy function as well as the KL divergence, we can conclude that…”
Section: 2mentioning
confidence: 90%
“…Interestingly, it was shown that this scenario does not offer any advantage, with relation to complete data compression. This setting, referred to as zero-rate communication, was recently revisited in [28] where both α n and β n are required to decrease exponentially with n.…”
mentioning
confidence: 99%
“…The finite length regime was investigated in [28]. The optimal Type-II error exponents of zerorate hypothesis testing in an interactive setup and in a cascaded-encoders network were presented respectively in [29] and [13], [16], [23], [30]. In particular, in our previous work [16], we proved such a result for the singlesensor two-detectors setup.…”
Section: Introductionmentioning
confidence: 77%
“…The latter scheme was shown to achieve the optimal exponent in the special case of testing against conditional independence by Rahman and Wagner [4]. This line of work has also been extended to networks with multiple sensors [2], [4]- [8], multiple detectors [9], interactive terminals [10]- [12], multi-hop networks [5], [13]- [16], noisy channels [17], [18], and scenarios with privacy constraints [19]- [22]. In this paper, we consider the single-sensor two-detectors system shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…This problem, which was first introduced by Berger [1], and then studied further in [2]- [4], arises naturally in many applications. Recent developments on this topic include extensions to networks with multiple sensors [5]- [9], multiple detectors [10], interactive terminals [11], [12], multi-hop networks [6], [13]- [16], noisy channels [17], [18] and scenarios with privacy constraints [19]- [21]. Its theoretical understanding, however, is far from complete, even from seemingly simple instances of it.…”
Section: Introductionmentioning
confidence: 99%